Per‐ and polyfluoroalkyl substances removal with granular activated carbon and a specialty adsorbent: A case study. Issue 5 (23rd September 2021) - Najm, Issam; Gallagher, Brian; Vishwanath, Nikhil; Blute, Nicole; Gorzalski, Alexander; Feffer, Adam; Richardson, Sarah
Abstract: Removal of per‐ and polyfluoroalkyl substances (PFAS) from water sources is of significant interest as many states have established limits. Three granular activated carbons (GACs) and a clay‐based adsorbent, Fluoro‐sorb® 200 (FS200), were tested using rapid small scale column tests (RSSCTs) to compare relative performance of the media for PFAS removal. FS200 effluent was below detection for all PFAS except PFHxA at 300, 000 bed volumes (BVs). The three GACs performed similarly except for PFBS and PFHxA. FS200 showed higher BVs to breakthrough, required a significantly shorter empty bed contact time, and had higher hydraulic loading rate, translating into a smaller footprint than GAC. This work provides important contributions to the water treatment literature, including RSSCT evaluation of FS200 media and media life comparison of GAC and FS200 in drinking water matrices with low PFAS and organic carbon concentrations. Article Impact Statement: Utilities needing PFAS treatment will benefit from the testing methodology and results.